Հայ-վրացական սահմանային-տարածքային վեճերը 1922-1936 թթ. - Նարեկ Մուրադյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В годы Закавказской Федерации армяно-грузинские территориальные споры в большинстве случаев были решены в пользу Грузии. Это логично, потому что комиссиями, которые занимались армяно-грузинскими проблемами, руководили либо грузины, либо азербайджанцы. During the years of Transcaucasian Federation, Armenian-Georgian territorial disputes have been solved in favour of Georgia. It is clearly understandable, because the committees regulating the Armenian-Georgian causes were headed by Georgian or Azeri figures.
Keywords: Armenian church; Christianity; Political Science; International relations; Fine Arts